STUDI TENTANG PEMBERIAN REMISI KEPADA PELAKU TINDAK PIDANA NARKOTIKA PADA LAPAS KLAS IIA AMBON - Denny Latumaerissa (Faculty of Law, Universitas Pattimura, 2017)
Implementation of criminal sanctions against narcotics criminals, good dealers, distributors and users, continue to be done considering the development of crime narcotics that is extraordinary crime continues to show a threat to the existence of this nation in the future. The existence of Tightening in remission, in this case to the perpetrator of special crime which inside such as perpetrator of narcotics crime, that is with existence of requirement specified in Government Regulation Number 99 year 2012 about condition and procedure of implementation of right of prisoners, especially to perpetrators of criminal narcotics criminally charged with imprisonment from five years and above, but in the application of narcotics criminals is still possible to get a remission. This is because the requirement must have a certificate of Justice collaborators, which is the status of justice collaborators although not provided by law enforcement officers but still can obtain remission.